Antibody repertoire analysis in polygenic autoimmune diseases - Bashford-Rogers, R; Smith, K; Thomas, D (Wiley, 2018)
High-throughput sequencing of the DNA/RNA encoding antibody heavy- and light-chains is rapidly transforming the field of adaptive immunity. It can address key questions, including: (i) how the B-cell repertoire differs in health and disease; and (ii) if it does differ, the point(s) in B-cell development at which this occurs. The advent of technologies, such as whole-genome sequencing, offers the chance to link abnormalities in the B-cell antibody repertoire to specific genomic variants and polymorphisms. Here, we discuss the current research using B-cell antibody repertoire sequencing in three polygenic autoimmune diseases where there is good evidence for a pathological role for B-cells, namely systemic lupus erythematosus, multiple sclerosis and rheumatoid arthritis. These autoimmune diseases exhibit significantly skewed B-cell receptor repertoires compared with healthy controls. Interestingly, some common repertoire defects are shared between diseases, such as elevated IGHV4-34 gene usage. B-cell clones have effectively been characterized and tracked between different tissues and blood in autoimmune disease. It has been hypothesized that these differences may signify differences in B-cell tolerance; however, the mechanisms and implications of these defects are not clear.